Faktor-Faktor yang Memengaruhi Penundaan Perkawinan Wanita Usia Dewasa Awal di Pulau Jawa Tahun 2024 - Oktavia, Elsa; Sitorus, Jeffry Raja Hamonangan (Politeknik Statistika STIS, 2025)
Marriage plays a vital role in a country’s demographic dynamics. However, Indonesia has seen a decline in marriage rates over the past decade. Changes in social and economic structures have contributed to the increasing phenomenon of delayed marriage, particularly among women. This trend has also influenced the Total Fertility Rate (TFR), especially in Java, where five out of six provinces reported a TFR below 2.1 in 2024. Delayed marriage among women is a critical issue due to its implications for reproductive health, as the reproductive age for women is limited to 15–49 years. This study analyzes factors influencing delayed marriage among ever-married women in early adulthood in Java Island in 2024. The method used is multilevel binary logistic regression. The results show that region classification, education level, employment status, savings ownership, and sex ratio significantly affect the likelihood of delayed marriage among this group of women.